STUDI DESKRIPTIF PELUANG KERJA ANAK TUNAGRAHITA PASCA SMALB NINDYA SEVA KUSMANINGSIH DAN SITI MAHMUDAH - Seva K., Nindya (Jurnal Pendidikan Khusus, 2017)
Abstract : Education for mentally retardation children in SMALB level was more emphasized to vocational skill which could be used as a provisions entering job fair. With the provisions of vocational skill it was hoped mentally retardation children obtained larger work opportunity after graduating from SMALB. However, that fact was not suitable with the expectation. Two mentally retardation children of 2014 graduation in state special school Gedangan did not get work opportunity and went back to school for only playing. The purposes of this research were to describe mentally retardation children’s work opportunity after graduating from SMALB with vocational skill provisions obtained from the school and to describe the parents’ role in helping mentally retardation children getting work opportunity after graduating from SMALB. This research used qualitative approach. The research kind used here was expose facto descriptive. The research result could be concluded that mentally retardation children who obtained the vocational skill provisions after graduating from school did not also obtain work opportunity in the society while mentally retardation children who obtained work opportunity after graduating from school had unsuitable job with the vocational skill they got from school. Mentally retardation children got vocational skill provisions in silk-screening domain but the work opportunity obtained was furniture domain, rubbing wood part. Mentally retardation children who had automotive background got work opportunity in the restaurant and mentally retardation children with the background of knitting vocational skill got work opportunity serving in the cooperation. The school did not give direction to the parents of mentally retardation children who had already graduated and the school did not have partners for cooperating in receiving the workers of mentally retardation children. The parents’ role in helping mentally retardation children did not run well yet. The parents’ role only gave food they did not help to give work yet to mentally retardation children who had already graduated. However, there was one parent who helped to market the work skill belonged to mentally retardation children and played role as the companion of mentally retardation children in working.     Keywords: Work opportunity, mentally retardation children, vocatinal skill, parents’ role